1991
DOI: 10.1034/j.1399-3054.1991.830115.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of lipid and protein reserves in loblolly pine seeds in relation to protein electrophoretic patterns following imbibition

Abstract: 1991. Hydrolysis of lipid and protein reserves in loblolly pine seeds in relation to protein electrophoretic patterns following imbibition The correlation between changes in seed protein electrophoretic patterns and the hydrolysis of lipid and protein reserves of loblolly pine (Pinus taeda L.) seed was studied. Seeds were incubated at 30°C for up to 12 days following stratification, then megagametophytes and embryos were assayed for lipid and protein content after each day of imbibition. The megagametophyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…11S legumin‐type seed storage proteins or their corresponding cDNAs have been characterized in many conifer species, principally based upon protein characterization or cDNA sequence analysis. These include several species of spruce (Misra and Green 1990, 1991, Hakman 1993), several species of pine (Gifford 1988, Groome et al 1991, Allona et al 1992, Baker et al 1996), two species of larch (Jensen and Lixue 1991), Douglas‐fir (Green et al 1991), dawn redwood (Häger and Dank 1996), cedar (Jensen and Lixue 1991), and incense cedar (Häger and Dank 1996). These proteins all share similar electrophoretic patterns, as well as a characteristic insolubility in buffer.…”
Section: Resultsmentioning
confidence: 99%
“…11S legumin‐type seed storage proteins or their corresponding cDNAs have been characterized in many conifer species, principally based upon protein characterization or cDNA sequence analysis. These include several species of spruce (Misra and Green 1990, 1991, Hakman 1993), several species of pine (Gifford 1988, Groome et al 1991, Allona et al 1992, Baker et al 1996), two species of larch (Jensen and Lixue 1991), Douglas‐fir (Green et al 1991), dawn redwood (Häger and Dank 1996), cedar (Jensen and Lixue 1991), and incense cedar (Häger and Dank 1996). These proteins all share similar electrophoretic patterns, as well as a characteristic insolubility in buffer.…”
Section: Resultsmentioning
confidence: 99%
“…1991, Misra and Green 1991, Hakman 1993, Stone and Gifford 1997, Chatthai and Misra 1998). Other studies have reported the identification of proteins that are believed to play important functional roles during specific developmental stages of embryogenesis such as late‐embryogenesis‐abundant (LEA) proteins, germination proteins and proteins involved in reserve hydrolysis (Stabel et al. 1990, Gifford et al.…”
Section: Introductionmentioning
confidence: 99%
“…ization during germination and early seedling growth , Hakman 1993, Stone and Gifford 1997, Chatthai and Misra 1998. Other studies have reported the identification of proteins that are believed to play important functional roles during specific developmental stages of embryogenesis such as late-embryogenesis-abundant (LEA) proteins, germination proteins and proteins involved in reserve hydrolysis , Groome et al 1991, Schneider and Gifford 1994. In contrast, limited data have been reported on events, which regulate early development of conifer zygotic embryos, mainly due to the relative inaccessibility of the embryos within the developing seeds.…”
Section: Introductionmentioning
confidence: 99%
“…In lobloily pine and other conifer seeds, stratification, important species produce seeds that are dormant, pos-germination and post-gertninative seedling growth are sess low germinability and/or have diminished seedling characterized by the accumulation and disappearance of vigor. To the forest industry, the recalcitrant nature of distinct de novo synthesized protein sets (Stabel et al conifer seed germination poses a significant problem to 1990, Gifford et al 1991, Groome et al 1991. Schneider the success and efficiency of reforestation, nursery prac-and Gifford 1994).…”
mentioning
confidence: 99%
“…A better understanding of seeds, electrophoretic analysis of proteins synthesized in vivo indicated that unique protein sets were synthesized in a temporal fashion. Gifford et al (1991) categorized these proteins into three groups; the first one is synthesized coostitutively throughout germination and postgerminative growth, the second one is present in the mature seed and is only synthesized for up to 1 day following imbibition at 28°C, and finally, a third one whose initial synthesis coincides with the completion of germination, and increases thereafter. In Norway spruce embryos, Stabel et al (1990) reported similar differential synthesis of protein sets during germination and postgerminative growth.…”
mentioning
confidence: 99%